2014
DOI: 10.1002/eat.22292
|View full text |Cite
|
Sign up to set email alerts
|

Eating behaviors and negative affect in college women's everyday lives

Abstract: Objective A growing body of research seeks to understand the relationship between mood and eating behaviors. Ecological Momentary Assessment (EMA) methods provide a method for assessing these processes in natural settings. We used EMA to examine the relationship between mood and eating behaviors in everyday life among women with subclinical disordered eating behaviors. Method Participants (N=127, age M=19.6, BMI M=25.5) completed 5 daily EMA reports on palmtop computers for 1 week. Assessments included measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 34 publications
1
41
2
Order By: Relevance
“…21 Meals and snacks that were not defined as restrictive were classified as non-restrictive. Of note, the current definition for a restrictive eating episode (i.e., “ate as little as possible” but not “ate an excessive amount of food”) is similar to that used in a recent EMA study of college women with subclinical disordered eating (i.e., “Did you try to limit the amount of food you ate?”), 22 providing support for the validity of this approach for assessing restrictive eating episodes.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…21 Meals and snacks that were not defined as restrictive were classified as non-restrictive. Of note, the current definition for a restrictive eating episode (i.e., “ate as little as possible” but not “ate an excessive amount of food”) is similar to that used in a recent EMA study of college women with subclinical disordered eating (i.e., “Did you try to limit the amount of food you ate?”), 22 providing support for the validity of this approach for assessing restrictive eating episodes.…”
Section: Methodsmentioning
confidence: 88%
“…26 In addition, this assessment approach is very similar to that used in a recent EMA study of college women with subclinical disordered eating for assessing restrictive eating (i.e., “Did you try to limit the amount of food you ate?”), providing additional support for its utility. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, a task for future research may be to consider how to use experimental paradigms to evaluate stressors more salient to specific youth at-risk for food disinhibition. Studies of self-reported disinhibited eating behavior in the natural environment frequently characterize negative affect as a single construct (Berg, et al, 2014; Heron, Scott, Sliwinski, & Smyth, 2014; Ranzenhofer, et al, 2014), and there may be meaningful differences in depressed versus stressed affect, for example. Whether the intensity of a specific emotional experience has an influence on energy intake is also an important area of future research.…”
Section: Discussionmentioning
confidence: 99%
“…Research estimates that approximately 8-13.5% of college women meet the criteria for clinically diagnosed eating disorders such as anorexia nervosa, bulima nervosa, or eating disorders not otherwise specified (Eisenberg, Nicklett, Roeder, & Kirz, 2011). In addition, negative moods (Heron, Scott, Sliwinski, & Smyth, 2014) and stress (Brewerton & Brady, 2014) seem to relate eating disorders. Diagnosable eating disorders emerge in the broader context of disordered eating, that is -engaging in practices such as restricting calories, eating less fat, skipping meals, using nonprescription diet pills, using laxatives, or inducing vomiting (Clemens, Thomb, Olds, & Gordon, 2008).…”
Section: Introductionmentioning
confidence: 99%